The Best Practices for Designing Built Environments to Promote Healthy Food Access and Dietary Behaviors in Low-Income and Underserved Communities - Ratodi, Muhamad; Zubaidah, Tien; Mei Lina Fitri Kumalasari; Esti Novi Andyarini (Universitas Airlangga, 2024)
Background: The built environment can influence health outcomes, including access to good dietary options. Aims: The current study intends to thoroughly evaluate the literature on best practices for building environments that promote healthy food access and nutritional behaviors in low-income and underserved communities in Indonesia. Method: To discover relevant studies on this topic, a thorough literature review was done using databases from PubMed, Web of Science, and Scopus extracting. Result: The final analysis included 32 studies after removing duplicates and applying inclusion and exclusion criteria. Extracting and assessing data from the chosen research and thematic synthesis was applied. The data was extracted and processed into a detailed narrative that provided an overview of the best practices. Conclusion: According to the findings of the literature study, built environment design can have a considerable impact on healthy food availability and eating patterns in Indonesian communities. It might be possible to develop effective interventions that enhance health outcomes for all Indonesians by addressing these gaps in the evidence.